Behavior Approach Model of Voluntary University Desertion in Undergraduate Programs in Engineering, Period 2015-2018 - Sánchez Arévalo, Mónica Lizeth; Cruz Hueso, Luisa Fernanda; Ferro Escobar, Roberto (Ingeniería Solidaria, 2018)
Introduction: This article is a research product of “Model Approach to University Dropout Behavior in Schools of Engineering” conducted during 2015-2017 at the Universidad Distrital Francisco José de Caldas. Problem: According to several preliminary studies, university education worldwide has deficiencies and problems that cause high dropout levels. Aim: To reveal student dropout levels and their impact on these programs nationally and internationally. Methods: To provide a national outlook, statistical reports of the problem were produced using the Higher Education Institution Dropout Prevention and Analysis System (spadie) tool. For a global view, data gathered by the World Bank and the United Nations Educational, Scientific and Cultural Organization (UNESCO) were used. Conclusion: Understanding education as a field continually exposed to change may give rise to strategies to mitigate shortcomings and ensure the presence of students. Results: The importance of monitoring the factors strengthens the statistical analysis by measuring and quantifying enrollment and dropout levels. Limitations: The little information provided by the Universidad Distrital hinders its analysis. Originality: An engineering student dropout analysis worldwide is presented and the creation of a compact base for the Universidad Distrital is proposed.